Evaluation of physical and mechanical properties of zirconia and alumina reinforced experimental nanohybrid dental luting composite cement using silica from rice husk - Islam, Md. Saiful (2022)
Aims: This study aimed to extract silica from the rice husk, then characterised the synthesised silica and commercial zirconia and alumina fillers to fabricate experimental nanohybrid dental luting composite cement (NHDLCC). The zirconia and alumina reinforced experimental NHDLCC were subjected for the evaluation of compressive strength, flexural strength, viscosity, water sorption and solubility testings. Materials and methods: The unsilanated nano silica from rice husk was characterized using a scanning electron microscope (SEM) equipped with energy dispersive X-ray (EDX). Silica, zirconia and alumina fillers were subjected to a surface treatment using silane coupling agents. All the silanated and unsilanated fillers were then characterized using Fourier transform infrared spectroscopy (FTIR). Three groups were fabricated based on different types of filler reinforcement: Group 1 (3 wt.% zirconia); Group 2 (3 wt.% alumina); Group 3 (3 wt.% zirconia and 2 wt.% alumina) whereas experimental NHDLCC without zirconia and alumina reinforcement was used as a negative control and a commercial nanohybrid dental luting composite, Rely-XTM U200 luting cement (3M ESPE; USA) was used as a positive control. All the experimental groups were then characterized using (SEM) equipped with (EDX) and subjected to its mechanical and physical properties evaluation that included compressive strength, flexural strength, viscosity, water sorption and solubility. Oneway ANOVA was used for multiple group comparison followed by post-hoc (Bonferroni) A statistically significant level was set at p = 0.05. Results: SEM and EDX confirmed the homogenously distributed spherical-shaped filler and the presence of filler particles in each group of expermental NHDLCC. The compressive strength of 3 wt.% zirconia reinforced filler group was found significantly higher when compared to the negative control (p < 0.05). Meanwhile, for the flexural strength, the water sorption and solubility, 3 wt.% zirconia and 2 wt.% alumina reinforced filler group showed significantly higher compared to the negative control (p < 0.05). For the viscosity testing, 3 wt.% alumina reinforced filler group showed statistically significant increase of viscosity compared to control at the oscillation frequency (ω) of 1 rad/s (p < 0.05). However, the difference was found not statistically significant at the oscillation frequency (ω) of 10 rad/s (p > 0.05) of NHDLCC. Conclusion: The silica was successfully extracted from the rice husk and all three fillers were characterised before and after surface treatment with the silane coupling agent. The reinforcement of different percentages of zirconia and alumina filler particles in the experimental NHDLCC improved compressive strength, flexural strength, viscosity properties, and decreased water sorption and solubility.